"Hortulus" 37, 1959: Translation as Collaboration in an Anthology of New Poetry from Israel - Rokem, Na'ama (Naharaim, 2024)
This article presents one issue of the Swiss literary journal Hortulus as a case study on forms of exchange, translation, and traffic between German and Hebrew in the wake of Nazism and World War II. Drawing on discussions in the field of Periodical Studies, I examine the various networks in which Hortulus 37 - a special issue devoted to new poetry from Israel - is situated. I highlight the heterogeneity of the volume, which contains materials translated into German from multiple languages, as well as original German texts. Translation itself appears in the volume as a heterogenous practice, which encompasses self-translation and various modes of collaborative translation. Since many of the authors who are translated into German in the volume were native speakers of that language, the lines between collaboration and self-translation are blurred in ways that have important consequences for our theorization of translation and self-translation.